CULTURAL PERCEPTIONS OF GENDER EQUALITY IN SPORTS AND ITS INFLUENCE ON FEMALE ATHLETE PARTICIPATION - Primanata, Dani (Gladi : Jurnal Ilmu Keolahragaan, 2024)
Abstract This study aims to explore the influence of cultural perceptions regarding gender equality on the participation of female athletes in sports. The type of research used is quantitative with a survey approach. The population in this study were female athletes who are active in various sports in Indonesia, and the sample consisted of 150 respondents who were selected randomly. The research instrument was a questionnaire that measured cultural perceptions and the level of participation of female athletes. The data analysis technique was carried out through linear regression analysis to test the relationship between variables. The results showed that cultural perceptions regarding gender equality had a positive and significant effect on the participation of female athletes, with a significance value of 0.000. As much as 39.3% of the variability in female athlete participation can be explained by cultural perceptions, while the rest is influenced by other factors such as social support and access to sports facilities. This study concludes that changes in cultural perceptions can encourage greater participation of female athletes in sports. To achieve this goal, collaboration is needed between various parties, including the government, sports organizations, and the media, to create an environment that supports gender equality in sports.